Bekasi pada Masa Kolonial (1925-1945) - Ramdiansyah, Pancar Catur (Historia Madania: Jurnal Ilmu Sejarah, 2022)
The colonial period in Indonesia was filled with several historical events. All of Indonesia's territory at that time was controlled by the colonialists. This also happened in the Bekasi area. This study will discuss the conditions of the Bekasi area during the colonial period. During the reign of the Dutch East Indies, Bekasi was one of the districts (kewedanan) of the regenschap of Meester Cornelis, the residency of Batavia. Then during the Japanese occupation between 1942-1945, it changed its name to Bekasi Gun. In addition, a review of the geographical conditions was also carried out when Bekasi was still a kewedanan. Then, the ethnic groups that occupy the Bekasi area are identified, namely the Sundanese, the Bekasi-Malay ethnic, and the Javanese ethnicity. Identification is also useful for getting a fairly clear picture of the cultural structure, social structure, economic structure, as well as the government system in Bekasi during the colonial period.